2013
DOI: 10.1002/cncr.28100
|View full text |Cite
|
Sign up to set email alerts
|

Matched‐pair and propensity score comparisons of outcomes of patients with clinical stage I non–small cell lung cancer treated with resection or stereotactic radiosurgery

Abstract: BACKGROUND: Stereotactic body radiotherapy (SBRT) is an alternative to surgery for clinical stage I non-small cell lung cancer (NSCLC), but comparing its effectiveness is difficult because of differences in patient selection and staging. METHODS: Two databases were combined which contained patients treated from 1999 to 2008 by lobectomy (LR, n 5 132), sublobar resection (SLR, n 5 48), and SBRT (n 5 137) after negative staging. Univariate and multivariate analysis were performed for survival (OS), total recurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
82
1
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 22 publications
(25 reference statements)
3
82
1
5
Order By: Relevance
“…This finding confirms that probably lower doses (thanpreviously thought) to the PTV edge may be sufficient to attainhigh control rates, as recently shown by Van Baardwijk et al in asystematic review of clinical trials [19].As in the DEGRO study, technical parameters did not influenceany clinical endpoint, and also the total number of SABR proceduresper Institution/year did not affect outcomes.Female gender was significantly correlated to a better distantprogressionfree survival and OS in a single report [8]. This findingwas not confirmed by our study or by other series, and this maybe due to the low number of female patients enrolled, hamperinga correct statistical evaluation, or to possible intrinsic differencesbetween Caucasian and Asian patients populations.A comparative matched-pair analysis including propensityscore (controlling for all factors affecting treatment selection)between two early stage NSCLC patients cohorts (180 treated withsurgery and 137 with SABR), showed that OS was comparable [20].At univariate analysis, OS was better for adenocarcinomas, smallertumor size and lower Charlson's comorbidity score, with no vari-ables selected as significantly affecting LC. At multivariate analysis,only Charlson's comorbidity index resulted associated to OS, whilelocal control was influenced by tumor size.…”
Section: Discussionmentioning
confidence: 99%
“…This finding confirms that probably lower doses (thanpreviously thought) to the PTV edge may be sufficient to attainhigh control rates, as recently shown by Van Baardwijk et al in asystematic review of clinical trials [19].As in the DEGRO study, technical parameters did not influenceany clinical endpoint, and also the total number of SABR proceduresper Institution/year did not affect outcomes.Female gender was significantly correlated to a better distantprogressionfree survival and OS in a single report [8]. This findingwas not confirmed by our study or by other series, and this maybe due to the low number of female patients enrolled, hamperinga correct statistical evaluation, or to possible intrinsic differencesbetween Caucasian and Asian patients populations.A comparative matched-pair analysis including propensityscore (controlling for all factors affecting treatment selection)between two early stage NSCLC patients cohorts (180 treated withsurgery and 137 with SABR), showed that OS was comparable [20].At univariate analysis, OS was better for adenocarcinomas, smallertumor size and lower Charlson's comorbidity score, with no vari-ables selected as significantly affecting LC. At multivariate analysis,only Charlson's comorbidity index resulted associated to OS, whilelocal control was influenced by tumor size.…”
Section: Discussionmentioning
confidence: 99%
“…Recently published papers show the matched-pair and propensity score comparison of resection and SABR (46). It is reported to have similar overall survival, local recurrence control and total recurrence control with SABR or surgery after controlling for prognostic and patient selection factors.…”
Section: Sabr For Patients With Operable Early Stage Lung Cancermentioning
confidence: 99%
“…It is reported to have similar overall survival, local recurrence control and total recurrence control with SABR or surgery after controlling for prognostic and patient selection factors. Using a propensity score to account for selection bias in the multivariate analysis provides the ability to control for the effects of greater numbers of variables and conduct analysis in the larger number of subjects (46).…”
Section: Sabr For Patients With Operable Early Stage Lung Cancermentioning
confidence: 99%
“…Porównania te miały charakter analiz bez uwzględnienia czynników rokowniczych [14], porównań z uwzględnieniem czynników rokowniczych z zastosowaniem doboru przypadków i grupy kontrolnej [12,[15][16][17][18], analiz wg modelu Markova [19,20], jak również metaanalizy wyników leczenia wczesnego raka płuca z wykorzystaniem SBRT vs chirurgii [21]. Wprawdzie czas przeżycia chorych operowanych analizowanych w tej ostatniej pracy był dłuższy w porównaniu z czasem przeżycia chorych poddanych SBRT, jednak 1-letnie i 3-letnie ryzyko zgonu z powodu nowotworu było takie same w obu grupach, co świadczy o negatywnej selekcji do grupy chorych poddanych radioterapii, prowadzącej do wyższego ryzyka zgonu z przyczyn pozanowotworowych.…”
Section: Stereotaktyczna Radioterapia Vs Chirurgia -Badania Porównawczeunclassified